Development of A Secured Database Access on Application Server - Ab Rashid, Siti Rosmaniza; Ismail, Mahamod (Science Academy Publisher, 2011)
Secured access is an important option in order to have access towards confidential information in database management system (DBMS). The network database system is usually open situation for information storage. Therefore, it is possible for the database to face any intruders or even being attack which can cause serious security problems. This research is done to develop a secured database access system on XAMPP and Limesurvey to observe the accessibility during different type of connection applied. Besides, this research also test the security designed in accessing the database and get some opinion from users through MOS evaluations.